Purificação e caracterização de um fator ansiolítico extraído da pele da leptodactylus labyrinthicus (Spix, 1824) - Nery, Marinetes Dantas de Aquino (1998)
Amphibian skin is full of glands that elaborate substances whose biological meaning is detached on: mucous glands that eliminate mucus keeping the skin humid for gas changes and protecting the animal against predators. Granular glands secrete poisons where peptides, proteins, guanidinic derived substances, biogenic amines, steroids and other compounds were found. On this study we isolated and punficated an anxiolytic faclor. The venom extracted frorn Leptodactylus labyrinthicus (spix, 1824) skin glands was obtained through an adrenaline subcutaneous injection (100 pg/ml). This lyophilized material is reduced to powder, where again it was resuspended in bidistiled water, centrifugated and the precipitate discarded. The supeniatant was fractionated by High Performance Liquid Chromatography (HPLC) using a Cl8 column (2,5x30 cm), eluted with a flow of 5 ml/min with a gradient of 5-80% acetonitrile. The fractions were lyophilized for bioassay. The separation’s products identified like peak 12, which showed tranquilization and a social behaviour different from Controls, when injected intraperitonially in mice and rats, was separated for behavioural studies. The chosen peak was passed once more at HPLC fine column (analytic column) which identified the purity degree, around 95%. The purified peak started to be studied in behavioural models such as the plus-maze test, staircase test, swimming test and the hole-board test. The peak in focus did not show any degree oftoxicity, not killing rats or mice. The plus-maze behaviour test is capable to measure anxiolytic drugs and the 12 peak was similar’ in comparison to benzodiazepines. The staircase test has also this capacity, combined with the hole-board exploratory activity. The swimming tests measures the anxiolytic drugs activity too and also induces depression in rats and mice, where the anxiolytic factor (12 peak) contributed to make evident their depressive State. The behavioural tests showed that the anxiolytic factor probably has it action mechanism in receptors similar to the benzodiazepine ones.